1978
DOI: 10.1007/bf01976038
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic transport of Tl+ in mitochondria

Abstract: The distribution of T1+ between rat liver mitochondria and the medium was studied; millimolar or smaller concentrations of T1+ were labeled with 204T1. The T1+ distribution responded to transient diffusion potentials in a way that indicated electrophoretic movements of T1+. The diffusion potentials were induced by efflux of K+ in response to addition of valinomycin to nonrespiring mitochondria suspended in a medium with low concentrations of K+ or by efflux of H+ induced by making the medium more alkaline in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Swelling of potassium-energized mitochondria in the 5-50 mM Tl acetate medium was markedly accelerated in the presence of nonactin ( Figure 2B). Taking into account these data, our findings argue in favor of nonactin facilitating electrophoretic transport of Tl + in energized mitochondria [3,9] (Figures 4B and 5). It was found that energized Na-loaded mitochondria swollen in 25 mM Tl acetate showed fast contraction, followed by deenergization [4].…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 60%
See 3 more Smart Citations
“…Swelling of potassium-energized mitochondria in the 5-50 mM Tl acetate medium was markedly accelerated in the presence of nonactin ( Figure 2B). Taking into account these data, our findings argue in favor of nonactin facilitating electrophoretic transport of Tl + in energized mitochondria [3,9] (Figures 4B and 5). It was found that energized Na-loaded mitochondria swollen in 25 mM Tl acetate showed fast contraction, followed by deenergization [4].…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 60%
“…Such a transport system can be the unregulated K + uniporter [3,6] or the K ATP channel of mitochondria [1,41] that are parts of the common transport mechanism for K + ions per se. Indeed, it was demonstrated earlier that these two parts, the nonregulated [3,4,7,9] and the regulated one [41], can be involved in energy-linked transport of Tl + in mitochondria. Another reason for the decrease may be amplification of the uncoupling effect of Tl + on the State 4 mitochondrial respiration in the presence of nonactin ( Figure 3A).…”
Section: Effect Of Nonactin On the Transport Of Tl + Via The Inner MImentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, no marked effect of Tl + on state 3 and 2,4-dinitrophenol(DNP)-stimulated respiration [2][3][4]6] and on mitochondrial respiratory enzymes [3,[8][9][10] was found. Considering that the inner mitochondrial membrane is easily permeable to Tl + [3,11], nonenergized mitochondria can markedly swell in TlNO 3 medium [6,7,12]. Subsequent energization of the mitochondria stimulated their contraction through the Tl + /H + exchange mechanism [6,7].…”
Section: Introductionmentioning
confidence: 99%